Pendampingan Manajemen Keuangan untuk Efisiensi Operasional pada Swalayan 777 Pekanbaru - Gusnafitri Gusnafitri; Dewi Martha; Ira Meike Andariyani; Rahma Yulita; Wirdayani Wahab (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity aims to increase financial managerial capacity and operational efficiency at Swalayan 777 Pekanbaru through structured financial management assistance. The main problems of partners include financial records that are not systematic, cash flow management that is still based on intuition, weak control of operational costs, and decision-making that is not based on financial data. The implementation method uses a participatory, educational, and problem-based mentoring approach through the stages of problem identification, observation, training, implementation assistance, and evaluation. The results of the activity showed an increase in managers' understanding of financial management, the formation of more structured financial recording practices, improvements in cash flow management, and the strengthening of operational cost control. In addition, there has been a change in managerial behavior towards decision-making that takes financial information into account. This activity shows that sustainable mentoring contributes positively to strengthening the governance and sustainability of retail businesses.